ประสบการณ์การเจ็บป่วยของผู้ป่วยวัยรุ่นโรคมะเร็งเม็ดเลือดขาว - สุรศักดิ์ ตรีนัย (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of this study was to describe illness experience of adolescent patients with leukemia. The Husserlian Phenomenology was applied as a methodology of the study. Data were collected by in-depth interview of 10 adolescent patients with leukemia. The interviews were taped and transcribed verbatim. The transcribed data were analyzed by using Colaizzi s method. (Colaizzi, 1978 cited in Streuberg and Carpenter, 1999). Findings revealed that illness experiences of adolescent patients with leukemia consisted of four themes, 1) Cancer is death : Adolescents connected the word "cancer" to their understanding of the severity of illness and the meaning of death 2) Fear of death because it is nearby : Fear of death was always kept in mind because adolescents thought that they would certainly die. 3) Enclosed by pain : Suffering from unavoidable physical and psychological pain which no one could understand. 4) Accepting the illness but not giving up : Accepting the illness as a part of their lives and trying tohave optimal lives. The findings of this study clearly reveal illness experience of adolescent patient with leukemia. They can be used as a data base for nursing practice and future research.